A high performance adsorption desulfurization catalyst and its preparation method and application

By using nano-level Group II B metal oxide support and Group VIII metal oxide components in adsorption and desulfurization catalysts, combining multifunctional additives and simplifying the preparation process, the problems of deep desulfurization and cost control in the prior art are solved, and the problem of deep desulfurization and cost control is achieved. High-efficiency and low-cost adsorption and desulfurization effect.

CN115999556BActive Publication Date: 2025-02-11CHEM & CHEM ENG GUANGDONG LAB
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202310081107.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-01-16
Publication Date
2025-02-11
Estimated Expiration
2043-01-16

AI Technical Summary

Technical Problem

The existing adsorption and desulfurization technology has challenges in deep desulfurization and cost control, especially the poor removal of complex sulfur-containing compounds, and the preparation process is complex and the cost is high.

Method used

Using nano-level Group II B metal oxide as support, introducing Group VIII metal oxide components, and adding multifunctional additives during the preparation process to avoid alumina support, simplify the preparation process, improve the diffusion performance of the catalyst and the active metal oxide dispersion.

Benefits of technology

The preparation of a high-performance adsorption and desulfurization catalyst is realized, which can reduce the sulfur content in the sulfur-containing liquid to the ppb level, meet environmental protection requirements, reduce production costs, and improve desulfurization efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115999556B_ABST
    Figure CN115999556B_ABST
Patent Text Reader

Abstract

The invention discloses a high-performance adsorption desulfurization catalyst and a preparation method and application thereof, belonging to the technical field of petrochemical industry. The high-performance adsorption desulfurization catalyst of the invention does not contain an alumina carrier, but directly uses a nano-scale group II B metal oxide as a carrier, then introduces a group VIII metal oxide component, and adds a multifunctional auxiliary agent during the preparation process, thereby improving the diffusion performance of the catalyst, while improving the dispersion of the active metal oxide component and the interaction between the components, thereby making the performance of the synthesized adsorption desulfurization catalyst more excellent, being able to reduce the sulfur content in sulfur-containing liquid to the ppb level, meeting environmental protection requirements, and having broad application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of petrochemical industry, and particularly relates to a method for preparing a high-performance adsorption desulfurization catalyst, and also relates to a high-performance adsorption desulfurization catalyst prepared by the preparation method, and also relates to an ultra-deep application of the high-performance adsorption desulfurization catalyst. Background Art

[0002] In recent years, with the continuous development of the economy and the continuous improvement of people's living standards, the demand for fuel oil in modern society has been growing. However, the sulfur-containing compounds in fuel oil are mainly discharged into the atmosphere in the form of sulfur dioxide after combustion. This acidic gas dissolves in small raindrops in the atmospheric environment and continues to accumulate to form acid rain, which has great damage and corrosion to industrial equipment, crops, buildings, etc. Therefore, the removal of sulfur-containing compounds in fuel oil has attracted widespread attention and has become one of the hot topics for researchers.

[0003] At present, the fuel oil desulfurization technologies widely used in industry are mainly hydrodesulfurization technology and adsorption desulfurization technology. Among them, hydrodesulfurization technology is the most commonly used desulfurization method. It usually uses hydrogen reduction and cracking of sulfur-containing compounds under high temperature and high pressure conditions of 300-350℃ and 3-5MPa under the action of catalysts such as Co-Mo / Al2O3 or Ni-Mo / Al2O3 to convert them into hydrogen sulfide and hydrocarbons, and then separate hydrogen sulfide from the system. This technology can effectively remove most simple organic sulfur-containing compounds such as ethyl mercaptan and disulfide from fuel oils such as gasoline and diesel, but it is not effective for some complex sulfur-containing compounds such as thiophene, benzothiophene, dibenzothiophene and Its derivatives are difficult to remove effectively without losing the octane number, so deep desulfurization is impossible, and the conditions are harsh, resulting in high desulfurization costs; while adsorption desulfurization technology is a method of removing sulfur-containing compounds from fuel oil under mild conditions, without the participation of hydrogen, through the adsorption effect of the adsorbent and the sulfur-containing compounds, the sulfur-containing compounds are adsorbed onto the adsorbent. This technology has good development scenarios and advantages, such as the octane number of the fuel oil after desulfurization is almost not reduced, the operating cost is relatively low, the reaction conditions are mild, and deep desulfurization can be achieved. Therefore, adsorption desulfurization is favored by researchers.

[0004] According to the specific adsorption principle, the adsorption desulfurization process can be divided into physical adsorption desulfurization and reactive adsorption desulfurization. Among them, physical adsorption desulfurization itself is based on the physical adsorption of sulfur-containing compounds on the surface of the adsorbent or the active components on its surface to remove Korean wave compounds. The adsorption process is simple and can remove sulfur-containing compounds at room temperature and pressure. The adsorbent is easy to regenerate and easy to commercialize. However, this method has poor selectivity for sulfides, low sulfur capacity, and is very easy to reach equilibrium. It is difficult to reduce the sulfur content to a very low level, so it is difficult to promote it in gasoline desulfurization. However, reactive adsorption desulfurization is a desulfurization method with better desulfurization performance. It removes sulfur atoms by means of the strong interaction between metal or metal oxide adsorbents and sulfur atoms. This desulfurization process has good selectivity and desulfurization performance and can achieve the purpose of deep desulfurization.

[0005] Whether it is physical adsorption desulfurization or reactive adsorption desulfurization, the key is the adsorbent. There are many types of adsorbents on the market with different effects. Therefore, developing an adsorbent with high selectivity and high sulfur capacity is the future development trend and goal of adsorption desulfurization technology.

[0006] CN 02109886.7 uses an impregnation method to prepare a desulfurizer of metal zinc modified activated carbon, which can remove the difficult-to-remove sulfide-dibenzothiophene and its derivatives in distillate oil. CN200810240549.2 uses a coprecipitation method to prepare an ultra-deep desulfurizer for a raw material containing carbon five conjugated dienes. The desulfurization adsorbent used is composed of group VIII and group IB metal oxides and an alumina carrier, which can reduce the sulfide content in the raw material containing carbon five conjugated dienes to 10ng / μl. CN103721668A uses a coprecipitation method to prepare an adsorbent composed of group VIII transition metals, group IB transition metals, group IIB transition metal oxides, group IVB metal oxides, group VIB metal oxides, group VIIB metal oxides, lanthanide metal oxides and alumina as a binder, which can reduce the sulfide content in FCC gasoline to 5ppm. CN101450302B adopts a coprecipitation method to prepare an adsorbent composed of a group VIII transition metal, a group IIB transition metal, a group IIB transition metal oxide and aluminum oxide, which can reduce the sulfur content in a C4 olefin raw material to 5ppm. CN102407094B adopts a combination of a coprecipitation method and an impregnation method to obtain an adsorbent composed of zinc oxide, VIB and / or group VIII metals, and a molecular sieve, which can adsorb almost all sulfides in gasoline while keeping the octane number unchanged.

[0007] The above desulfurization adsorbents mainly use a variety of metals and metal oxides as the main body of the adsorbent or alumina as the adsorbent carrier. In terms of the preparation method alone, due to the excessive variety of metals and metal oxides, in order to obtain the adsorbent body composed of a variety of metals and metal oxides, the usual approach is to dissolve the soluble salts of a variety of metals in water to prepare a solution, or to adopt a multi-step precipitation reaction or a multi-step impregnation, ion exchange and other methods, and the preparation process is cumbersome. In the preparation process, alumina is mostly used as an ion exchange or impregnation adsorbent carrier. However, these methods generally have the following disadvantages: 1. Adding alumina to the adsorbent will reduce the proportion of metal components, thereby affecting the adsorption rate of the molded adsorbent and increasing the amount of adsorbent used; 2. The preparation of alumina carriers requires the addition of peptizing agents such as nitric acid and adhesives such as alumina during the adsorbent molding process, which will increase the cost of the adsorbent; 3. Under high temperature conditions during adsorption desulfurization and repeated regeneration, the alumina carrier will interact with the active metal oxide components to generate spinel phases and alloy phases, thereby causing active component loss and aggregation effects, which ultimately affect the dispersion of active metal oxide components and interactions between them.

[0008] In summary, adsorption desulfurizer is crucial for its full promotion. Therefore, developing an adsorption desulfurizer with excellent performance will become a decisive factor in the future development of fuel oil desulfurization. Summary of the invention

[0009] The present invention provides a high-performance adsorption desulfurization catalyst after extensive research on existing desulfurization adsorbents, wherein the active metal oxide component is relatively small and the preparation process is simple. In particular, the high-performance adsorption desulfurization catalyst does not contain an alumina carrier, and directly uses a nano-scale IIB group metal oxide as a carrier, and then introduces a group VIII metal oxide component, and adds a multifunctional auxiliary agent during the preparation process, thereby achieving improved diffusion performance of the catalyst, while improving the dispersion of the active metal oxide component and the interaction between the components, thereby making the performance of the synthesized adsorption desulfurization catalyst more excellent, and can reduce the sulfur content in the sulfur-containing liquid to the ppb level, meet environmental protection requirements, and have broad application prospects.

[0010] In a first aspect of the present invention, the present invention provides a method for preparing a high-performance adsorptive desulfurization catalyst, which comprises the following steps:

[0011] (S1) uniformly mixing a Group IIB metal oxide, a multifunctional additive, a lubricant and a soluble salt of a Group VIII metal to obtain a solid mixture;

[0012] (S2) dissolving a soluble salt of a Group VIII metal in water to obtain a soluble salt solution of the Group VIII metal;

[0013] (S3) homogenizing the solid mixture obtained in step (S1) and the soluble salt solution of the Group VIII metal obtained in step (S2) and subjecting the mixture to molding to obtain a desulfurization catalyst molded body;

[0014] (S4) Drying and calcining the desulfurization catalyst molded body obtained in step (S3) to obtain the high performance adsorption desulfurization catalyst of the present invention.

[0015] The order of step (S1) and step (S2) is not strictly limited and can be adjusted according to the situation. They can be performed simultaneously, or step (S1) can be performed first, and of course step (S2) can also be performed first.

[0016] Generally, the adsorbent used in reactive adsorption desulfurization is also called an adsorption desulfurization catalyst. The present invention uses Group IIB metal oxide as a carrier, introduces soluble salts of Group VIII metals thereon in the form of solid and solution, and introduces Group VIII metal oxide into Group IIB metal oxide after calcination, thereby avoiding the problem of aggregation of active species of Group VIII metal oxide that exists when Group VIII metal oxide is introduced into Group IIB metal oxide in liquid form (impregnation or precipitation), thereby leading to a decrease in the adsorption desulfurization performance of the catalyst.

[0017] Preferably, in the above method, the amounts of the Group IIB metal oxide, the multifunctional additive, the lubricant and the soluble salt of the Group VIII metal in step (S1) are, in parts by weight, respectively:

[0018]

[0019]

[0020] Further preferably, in the above method, the amounts of the Group IIB metal oxide, the multifunctional additive, the lubricant and the soluble salt of the Group VIII metal in the step (S1) are, in parts by weight, respectively:

[0021]

[0022] In step (S1) of the method, the Group IIB metal oxide, multifunctional additive, lubricant and soluble salt of Group VIII metal are within a suitable ratio range so that the active species can be evenly dispersed and not easily aggregated when the solids are mixed with the soluble salt solution of Group VIII metal.

[0023] Preferably, in the above method, the particle size of the Group IIB metal oxide in step (S1) is 20-50 nm. At this particle size, the dispersion of the Group VIII metal oxide on the surface of the nanoscale Group IIB metal oxide can be improved, thereby improving the interaction between the two types of metal oxides, and ultimately increasing the number of active sites, which is beneficial to improving the catalyst activity and sulfur capacity.

[0024] Preferably, in the above method, the Group IIB metal oxide in the step (S1) is zinc oxide. The present invention does not use aluminum oxide as a carrier, but directly uses zinc oxide as a carrier, so there is no interaction between the aluminum oxide carrier and the Group VIII metal oxide, thereby avoiding the phenomenon of reduced catalyst activity caused by the reaction between the two to form a spinel phase during the adsorption desulfurization and regeneration process, and can reduce production costs, which is conducive to the promotion and use of the adsorption desulfurization catalyst of the present invention.

[0025] Preferably, in the above method, the multifunctional auxiliary agent in step (S1) is one or more of sodium carboxymethyl cellulose, potassium carboxymethyl cellulose, sodium alginate, sodium polyacrylate, sodium carboxyethyl cellulose, and more preferably sodium carboxymethyl cellulose. These multifunctional auxiliary agents, on the one hand, act as pore formers, and can form a developed pore structure in the obtained high-performance adsorption desulfurization catalyst, which is conducive to the diffusion of sulfur-containing materials; on the other hand, they act as dispersants, and the alkali metal cations in the multifunctional auxiliary agents can increase the mutual repulsion of the two components when the group VIII metal ions are loaded on the group IIB metal oxides, thereby reducing the aggregation of the group VIII metal oxides, and finally improving the dispersion of the group VIII metal oxides on the group IIB metal oxides, so that the desulfurization performance is improved.

[0026] Preferably, in the above method, the mass ratio of the IIB group metal oxide to the multifunctional auxiliary agent in the step (S1) is (30-40): 1. If the amount of the multifunctional auxiliary agent is insufficient, the pore structure formed in the obtained high-performance adsorption desulfurization catalyst is not well developed, which is not conducive to the diffusion of sulfur-containing materials, and the group VIII metal oxide is prone to aggregation; and if the amount of the multifunctional auxiliary agent is too much, the interaction between the IIB group metal oxide and the group VIII metal ion is significantly reduced due to the excessively strong charge repulsion, which leads to the inability of the group VIII metal oxide to be effectively loaded on the IIB metal oxide, so that the active sites formed by the interaction between the IIB metal oxide and the group VIII metal in the formed adsorption desulfurization catalyst are less, and the desulfurization effect is finally reduced.

[0027] Preferably, in the above method, the lubricant in step (S1) is sesbania powder or graphite powder, and sesbania powder is more preferably.

[0028] In the present invention, both graphite powder and sesbania powder can be used as lubricants, which is beneficial to the molding in the step (S3). However, compared with graphite powder, sesbania powder is more environmentally friendly. This is because sesbania powder is obtained by crushing and sieving the endosperm of sesbania seeds of the leguminous plant. Its main components are galactose and mannose, and it has good water solubility, high viscosity, crosslinking properties, and good flocculation and salt resistance.

[0029] Preferably, in the above method, the mass ratio of the IIB group metal oxide to the lubricant in the step (S1) is (90-100): 1. If the amount of lubricant is insufficient, the lubrication effect is poor, which is not conducive to demoulding during the molding process in the step (S3), thereby causing the obtained adsorption desulfurization catalyst to collapse; however, if the amount of lubricant is too much, the demoulding will be too fast during the molding process in the step (S3) due to excessive lubricity, thereby causing the mechanical strength of the obtained adsorption desulfurization catalyst to be low. In addition, if the amount of lubricant is too much, the proportion of active metal oxide components in the adsorption desulfurization catalyst will be reduced, affecting the desulfurization effect of the obtained adsorption desulfurization catalyst, and at the same time increasing the amount of adsorption desulfurization catalyst used, thereby increasing the desulfurization cost.

[0030] Preferably, in the above method, the soluble salt of the Group VIII metal is one or more of the nitrate, acetate, sulfate and chloride of the Group VIII metal, and further preferably is one or more of nickel nitrate, nickel acetate, nickel sulfate, nickel chloride, cobalt nitrate, cobalt acetate, cobalt sulfate and cobalt chloride. However, based on cost and performance considerations, nickel acetate is most preferred.

[0031] Preferably, in the above method, the mass ratio of the amount of the soluble salt of the Group VIII metal in the step (S1) to the amount of the soluble salt of the Group VIII metal in the step (S2) is (1-2): 1. The Group VIII metal oxide in the adsorption desulfurization catalyst of the present invention is introduced into the catalyst twice in the form of a solid and a solution of a Group VIII soluble metal salt through steps (S1) and (S2), respectively, which can avoid the problem of aggregation of active species of the Group VIII metal oxide in the adsorption desulfurization catalyst prepared when the Group VIII metal oxide is introduced into the Group IIB metal oxide in liquid form (impregnation or precipitation), thereby overcoming the phenomenon of decreased adsorption desulfurization performance of the catalyst caused by this.

[0032] Preferably, in the above method, the mass fraction of the soluble salt of the Group VIII metal in the soluble salt solution of the Group VIII metal obtained in the step (S2) is 10-20%, more preferably 10-16.5%.

[0033] Preferably, in the above method, the water used in step (S2) is deionized water or other water with a resistivity greater than 0.5 megohm.cm to avoid the introduction of other impurities.

[0034] Preferably, in the above method, the molding process in step (S3) includes extrusion molding, tablet molding, ball molding or spray granulation molding. The high-performance adsorption desulfurization catalyst of the present invention can only be loaded into the adsorption tower or adsorption column for use after molding, so that the sulfur-containing material can flow through the gaps between the particles. If the adsorption desulfurization catalyst is in powder form, the fluidity of the sulfur-containing material, especially the sulfur-containing fuel oil, will deteriorate and cause blockage. In addition, the powdered adsorption desulfurization catalyst will also remain in the sulfur-containing fuel oil, thereby polluting the fuel oil. Therefore, molding treatment is required to ensure that the final adsorption desulfurization catalyst is in a non-powdered form.

[0035] In the present invention, the extrusion molding operation process is to first transfer the material mixture to a kneader, and then transfer it to an extruder for extrusion molding. The specific operation process of the tableting molding is to first granulate the material in a granulator, and then place the granulator product in a tablet press for tableting molding. It should be noted that the present invention has no strict restrictions on the molding process and method, as long as the adsorption desulfurization catalyst obtained is finally guaranteed to be non-powdery.

[0036] Preferably, in the above method, the drying conditions in step (S4) are: temperature of 110-130° C. and time of 12-24 h.

[0037] Preferably, in the above method, the conditions for calcination in step (S4) are: in an air atmosphere or an oxygen atmosphere, the temperature is 550-600°C, and the time is 4-10h. This calcination process is to remove the lubricant and the multifunctional additive to avoid the adverse effect of the presence of the two on the performance of the adsorption desulfurization catalyst. In addition, in the process of calcination to remove the lubricant and the multifunctional additive, a pore-forming effect can be played, and a certain amount of pores can be formed in the adsorption desulfurization catalyst, which is conducive to the diffusion of sulfur-containing materials. At the same time, this calcination can make the obtained adsorption desulfurization catalyst have a certain structural strength.

[0038] The present invention introduces Group VIII metal elements in solid and liquid forms, respectively, thereby avoiding aggregation, and further avoiding the phenomenon of decreased desulfurization performance due to aggregation. The preparation method of the present invention is simple and does not require strict process control, which is conducive to large-scale industrial production, thereby providing a premise and basis for subsequent large-scale applications.

[0039] In addition, in a second aspect of the present invention, a high-performance adsorptive desulfurization catalyst is provided, which is composed of a Group IIB metal oxide and at least one Group VIII metal oxide.

[0040] The high-performance adsorption desulfurization catalyst of the present invention does not add an alumina carrier, so there is no interaction between the alumina carrier and the Group VIII metal oxide, thereby avoiding the problem of reduced catalyst activity caused by the reaction between the two to form a spinel phase during the adsorption desulfurization and regeneration process.

[0041] Preferably, in the above-mentioned high-performance adsorptive desulfurization catalyst, the particle size of the Group IIB metal oxide is 20-50 nm.

[0042] Preferably, in the above-mentioned high-performance adsorptive desulfurization catalyst, the Group IIB metal oxide is zinc oxide.

[0043] Preferably, in the above-mentioned high-performance adsorptive desulfurization catalyst, the Group VIII metal oxide is nickel oxide and / or cobalt oxide, more preferably nickel oxide.

[0044] Preferably, in the above-mentioned high-performance adsorptive desulfurization catalyst, based on the total weight of the high-performance adsorptive desulfurization catalyst, the mass fraction of the IIB group metal oxide is 90-98%, and the mass fraction of the VIII group metal oxide is 2-10%.

[0045] Preferably, the high-performance adsorption desulfurization catalyst is prepared by the above method, which does not use multi-step precipitation reaction or multi-step impregnation, ion exchange and other steps, and the process is simple, which is conducive to industrial application.

[0046] In addition, in a third aspect of the present invention, the present invention provides an application of the above-mentioned high-performance adsorptive desulfurization catalyst, wherein the application is used for desulfurization treatment of sulfur-containing liquids.

[0047] The adsorption desulfurization catalyst of the present invention has significant improvements in both desulfurization activity and sulfur capacity, especially in desulfurization activity, and can reduce the sulfur content of raw gasoline to below 100 ng / Kg.

[0048] Preferably, in the above application, the sulfur-containing liquid is one or more of sulfur-containing isopentane, isopentene, cyclopentane, cyclopentene, methylcyclopentane, methylcyclopentene, n-hexane, n-hexene, cyclohexane, cyclohexene, methylcyclohexane, methylcyclohexene, n-heptane, n-heptene, gasoline and diesel.

[0049] Preferably, in the above application, the specific process of the desulfurization treatment is to use a fixed bed for treatment. Before the adsorption desulfurization, the high-performance adsorption desulfurization catalyst needs to be reduced in an atmosphere containing H2 at a temperature of 350-450°C for 5-10h. The operating conditions of the high-performance adsorption desulfurization catalyst for desulfurization of sulfur-containing liquids are: adsorption temperature 300-400°C, hydrogen partial pressure 0.1-2MPa, hydrogen to desulfurization liquid volume ratio (10-1000): 1, and the volume space velocity of the sulfur-containing liquid is 2-30h. -1 .

[0050] Compared with the prior art, the present invention has the following beneficial effects:

[0051] (1) The high-performance adsorptive desulfurization catalyst of the present invention uses nano-sized Group IIB metal oxide as a carrier, directly loads Group VIII metal oxide on the nano-sized Group IIB metal oxide, and introduces Group VIII metal elements onto the nano-sized Group IIB metal oxide twice in the form of a solid and a solution of a soluble salt of the Group VIII metal during the preparation process, thereby avoiding the phenomenon of aggregation of active species of the Group VIII metal oxide that occurs when the Group VIII metal elements are introduced entirely into the nano-sized Group IIB metal oxide in liquid form (impregnation or precipitation), thereby avoiding the problem of decreased adsorptive desulfurization performance of the catalyst caused by this.

[0052] 2. The active components of the high-performance adsorption desulfurization catalyst of the present invention are composed of only one nano-scale Group IIB metal oxide and at least one Group VIII metal oxide. No alumina carrier is used, and there is no interaction between the alumina carrier and the Group VIII metal oxide, thereby avoiding the problem of reduced catalyst activity caused by the reaction between the two to form a spinel phase during the adsorption desulfurization and regeneration process.

[0053] 3. The preparation method of the present invention adds a multifunctional additive during the preparation process, which is not only beneficial to molding, but also beneficial to improving the dispersion of the nano-scale IIB group metal oxide and the pore structure properties of the prepared catalyst, thereby improving the diffusion performance of the obtained catalyst. In addition, the preparation method of the present invention can also improve the dispersion of the VIII group metal oxide on the surface of the nano-scale IIB group metal oxide, thereby improving the interaction between the two types of metal oxides, and ultimately increasing the number of active sites, which is beneficial to improving the catalyst activity and sulfur capacity. BRIEF DESCRIPTION OF THE DRAWINGS

[0054] Figure 1 XRD diagrams of the adsorption desulfurization catalyst prepared in Example 1 of the present invention and the products prepared in Comparative Examples 2-4;

[0055] Figure 2H2 pulse chemical adsorption diagrams of the adsorption desulfurization catalyst prepared in Example 1 of the present invention and the products prepared in Comparative Examples 2-4;

[0056] Figure 3 H2-TPR diagram of the adsorption desulfurization catalyst prepared in Example 1 of the present invention and the products prepared in Comparative Examples 2-4;

[0057] Figure 4 XPS graphs of the adsorptive desulfurization catalyst prepared in Example 1 of the present invention and the products prepared in Comparative Examples 2-4. DETAILED DESCRIPTION

[0058] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the technical solutions of the present invention will be described in detail with specific embodiments below.

[0059] In the following examples, the water used is deionized water to avoid the introduction of unnecessary impurities. The nickel acetate is nickel acetate tetrahydrate, which is purchased from Sinopharm Chemical Reagent Co., Ltd., analytically pure, and the nickel acetate content is 70%. The roasting involved in the following examples is carried out under air atmosphere unless otherwise specified.

[0060] Embodiments of the invention

[0061] Invention Example 1

[0062] (S1) 1940 g of nano ZnO (particle size 30 nm), 60 g of sodium methyl cellulose, 20 g of tianqing powder, and 120 g of nickel acetate tetrahydrate were mixed to obtain a solid mixture;

[0063] (S2) dissolving 80 g of nickel acetate tetrahydrate in 490 g of water to obtain a nickel acetate solution;

[0064] (S3) uniformly mixing the nickel acetate solution of Group VIII metal obtained in step (S2) and the solid mixture obtained in step (S1), then transferring the materials to a kneader for kneading twice, and finally placing them in an extruder for extrusion molding to obtain a desulfurization catalyst molded body;

[0065] (S4) The desulfurization catalyst molded body obtained in the step (S3) is dried at 110° C. for 12 hours, and then calcined at 550° C. for 6 hours to obtain a high-performance adsorption desulfurization catalyst of the present invention, denoted as A1, wherein the mass ratio of zinc oxide to nickel oxide is 32.31.

[0066] Invention Example 2

[0067] (S1) 1900 g of nano ZnO (particle size 30 nm), 60 g of sodium methyl cellulose, 20 g of tianqing powder, and 160 g of nickel acetate tetrahydrate were mixed to obtain a solid mixture;

[0068] (S2) dissolving 80 g of nickel acetate tetrahydrate in 490 g of water to obtain a nickel acetate solution;

[0069] (S3) uniformly mixing the nickel acetate solution of Group VIII metal obtained in step (S2) and the solid mixture obtained in step (S1), then transferring the materials to a kneader for kneading twice, and finally placing them in an extruder for extrusion molding to obtain a desulfurization catalyst molded body;

[0070] (S4) The desulfurization catalyst molded body obtained in the step (S3) is dried at 110° C. for 12 hours, and then calcined at 580° C. for 8 hours to obtain a high-performance adsorption desulfurization catalyst of the present invention, denoted as A2, wherein the mass ratio of zinc oxide to nickel oxide is 26.37.

[0071] Invention Example 3

[0072] (S1) 1800 g of nano ZnO (particle size of 25 nm), 50 g of sodium methyl cellulose, 15 g of tianqing powder, and 120 g of nickel acetate tetrahydrate were mixed to obtain a solid mixture;

[0073] (S2) dissolving 80 g of nickel acetate tetrahydrate in 490 g of water to obtain a nickel acetate solution;

[0074] (S3) uniformly mixing the nickel acetate solution of Group VIII metal obtained in step (S2) and the solid mixture obtained in step (S1), then transferring the materials to a kneader for kneading twice, and finally placing them in an extruder for extrusion molding to obtain a desulfurization catalyst molded body;

[0075] (S4) The desulfurization catalyst molded body obtained in the step (S3) is dried at 110° C. for 12 hours, and then calcined at 550° C. for 6 hours to obtain a high-performance adsorption desulfurization catalyst of the present invention, denoted as A3, wherein the mass ratio of zinc oxide to nickel oxide is 29.98.

[0076] Invention Example 4

[0077] (S1) 1940 g of nano ZnO (particle size 30 nm), 60 g of sodium methyl cellulose, 40 g of tianqing powder, and 80 g of nickel acetate tetrahydrate were mixed to obtain a solid mixture;

[0078] (S2) dissolving 80 g of nickel acetate tetrahydrate in 490 g of water to obtain a nickel acetate solution;

[0079] (S3) uniformly mixing the nickel acetate solution of Group VIII metal obtained in step (S2) and the solid mixture obtained in step (S1), then transferring the materials to a kneader for kneading twice, and finally placing them in an extruder for extrusion molding to obtain a desulfurization catalyst molded body;

[0080] (S4) The desulfurization catalyst molded body obtained in the step (S3) is dried at 110° C. for 12 hours, and then calcined at 550° C. for 6 hours to obtain a high-performance adsorption desulfurization catalyst of the present invention, denoted as A4, wherein the mass ratio of zinc oxide to nickel oxide is 40.38.

[0081] Invention Example 5

[0082] (S1) 1800 g of nano ZnO (particle size 30 nm), 55 g of sodium methyl cellulose, 20 g of tianqing powder, and 140 g of nickel acetate tetrahydrate were mixed to obtain a solid mixture;

[0083] (S2) dissolving 80 g of nickel acetate tetrahydrate in 490 g of water to obtain a nickel acetate solution;

[0084] (S3) uniformly mixing the nickel acetate solution of Group VIII metal obtained in step (S2) and the solid mixture obtained in step (S1), then transferring the materials to a kneader for kneading twice, and finally placing them in an extruder for extrusion molding to obtain a desulfurization catalyst molded body;

[0085] (S4) The desulfurization catalyst molded body obtained in the step (S3) is dried at 110° C. for 12 hours, and then calcined at 550° C. for 6 hours to obtain a high-performance adsorption desulfurization catalyst of the present invention, denoted as A5, wherein the mass ratio of zinc oxide to nickel oxide is 27.25.

[0086] Invention Example 6

[0087] (S1) 1500 g of nano ZnO (particle size of 25 nm), 50 g of sodium methyl cellulose, 16 g of tianqing powder, and 120 g of nickel acetate tetrahydrate were mixed to obtain a solid mixture;

[0088] (S2) dissolving 90 g of nickel acetate tetrahydrate in 490 g of water to obtain a nickel acetate solution;

[0089] (S3) uniformly mixing the nickel acetate solution of Group VIII metal obtained in step (S2) and the solid mixture obtained in step (S1), then transferring the materials to a kneader for kneading twice, and finally placing them in an extruder for extrusion molding to obtain a desulfurization catalyst molded body;

[0090] (S4) The desulfurization catalyst molded body obtained in the step (S3) is dried at 110° C. for 12 hours, and then calcined at 550° C. for 6 hours to obtain a high-performance adsorption desulfurization catalyst of the present invention, denoted as A6, wherein the mass ratio of zinc oxide to nickel oxide is 23.79.

[0091] Invention Example 7

[0092] (S1) 1940 g of nano ZnO (particle size 30 nm), 60 g of sodium methyl cellulose, 20 g of tianqing powder, and 120 g of nickel acetate tetrahydrate were mixed to obtain a solid mixture;

[0093] (S2) dissolving 80 g of nickel acetate tetrahydrate in 300 g of water to obtain a nickel acetate solution;

[0094] (S3) uniformly mixing the nickel acetate solution of Group VIII metal obtained in step (S2) and the solid mixture obtained in step (S1), then transferring the materials to a kneader for kneading twice, and finally placing them in an extruder for extrusion molding to obtain a desulfurization catalyst molded body;

[0095] (S4) The desulfurization catalyst molded body obtained in the step (S3) is dried at 110° C. for 8 hours, and then calcined at 580° C. for 7 hours to obtain a high-performance adsorption desulfurization catalyst of the present invention, denoted as A7, wherein the mass ratio of zinc oxide to nickel oxide is 32.31.

[0096] Invention Example 8

[0097] (S1) 2000 g of nano ZnO (particle size 40 nm), 60 g of sodium methyl cellulose, 20 g of tianqing powder, and 120 g of nickel acetate tetrahydrate were mixed to obtain a solid mixture;

[0098] (S2) dissolving 80 g of nickel acetate tetrahydrate in 490 g of water to obtain a nickel acetate solution;

[0099] (S3) uniformly mixing the nickel acetate solution of Group VIII metal obtained in step (S2) and the solid mixture obtained in step (S1), then transferring the materials to a kneader for kneading twice, and finally placing them in an extruder for extrusion molding to obtain a desulfurization catalyst molded body;

[0100] (S4) The desulfurization catalyst molded body obtained in the step (S3) is dried at 120° C. for 18 hours, and then calcined at 600° C. for 9 hours to obtain a high-performance adsorption desulfurization catalyst of the present invention, denoted as A8, wherein the mass ratio of zinc oxide to nickel oxide is 33.31.

[0101] Comparative Example

[0102] Comparative Example 1

[0103] (S1) 1940 g of nano ZnO (particle size 30 nm), 60 g of sodium methyl cellulose, and 20 g of Tianqing powder were mixed to obtain a solid mixture;

[0104] (S2) mixing the 490 g water and the solid mixture obtained in step (S1) uniformly, then transferring the material to a kneader and kneading it twice, and finally placing it in an extruder for extrusion molding to obtain a desulfurization catalyst molded body;

[0105] (S3) The desulfurization catalyst molded body obtained in the step (S2) is dried at 110° C. for 12 hours, and then calcined at 550° C. for 6 hours to obtain a product, which is recorded as B1.

[0106] Comparative Example 2

[0107] (S1) 1940 g of nano ZnO (particle size 30 nm), 20 g of Tianqing powder, and 120 g of nickel acetate tetrahydrate were mixed to obtain a solid mixture;

[0108] (S2) dissolving 80 g of nickel acetate tetrahydrate in 490 g of water to obtain a nickel acetate solution;

[0109] (S3) uniformly mixing the nickel acetate solution of Group VIII metal obtained in step (S2) and the solid mixture obtained in step (S1), then transferring the materials to a kneader for kneading twice, and finally placing them in an extruder for extrusion molding to obtain a desulfurization catalyst molded body;

[0110] (S4) The desulfurization catalyst molded body obtained in the step (S3) is dried at 110° C. for 12 hours, and then calcined at 550° C. for 6 hours to obtain a product, which is recorded as B2.

[0111] Comparative Example 3

[0112] (S1) 1940 g of nano ZnO (particle size 30 nm), 20 g of sodium methyl cellulose, 20 g of tianqing powder, and 120 g of nickel acetate tetrahydrate were mixed to obtain a solid mixture;

[0113] (S2) dissolving 80 g of nickel acetate tetrahydrate in 490 g of water to obtain a nickel acetate solution;

[0114] (S3) uniformly mixing the nickel acetate solution of Group VIII metal obtained in step (S2) and the solid mixture obtained in step (S1), then transferring the materials to a kneader for kneading twice, and finally placing them in an extruder for extrusion molding to obtain a desulfurization catalyst molded body;

[0115] (S4) The desulfurization catalyst molded body obtained in the step (S3) is dried at 110° C. for 12 hours, and then calcined at 550° C. for 6 hours to obtain a product, which is recorded as B3.

[0116] Comparative Example 4

[0117] (S1) 1940 g of nano ZnO (particle size 30 nm), 60 g of starch, 20 g of Tianqing powder, and 120 g of nickel acetate tetrahydrate were mixed to obtain a solid mixture;

[0118] (S2) dissolving 80 g of nickel acetate tetrahydrate in 490 g of water to obtain a nickel acetate solution;

[0119] (S3) uniformly mixing the nickel acetate solution of Group VIII metal obtained in step (S2) and the solid mixture obtained in step (S1), then transferring the materials to a kneader for kneading twice, and finally placing them in an extruder for extrusion molding to obtain a desulfurization catalyst molded body;

[0120] (S4) The desulfurization catalyst molded body obtained in the step (S3) is dried at 110° C. for 12 hours, and then calcined at 550° C. for 6 hours to obtain a product, which is recorded as B4.

[0121] Comparative Example 5

[0122] (S1) 1940 g of nano ZnO (particle size 30 nm), 195 g of sodium methyl cellulose, 20 g of tianqing powder, and 120 g of nickel acetate tetrahydrate were mixed to obtain a solid mixture;

[0123] (S2) dissolving 80 g of nickel acetate tetrahydrate in 490 g of water to obtain a nickel acetate solution;

[0124] (S3) uniformly mixing the nickel acetate solution of Group VIII metal obtained in step (S2) and the solid mixture obtained in step (S1), then transferring the materials to a kneader for kneading twice, and finally placing them in an extruder for extrusion molding to obtain a desulfurization catalyst molded body;

[0125] (S4) The desulfurization catalyst molded body obtained in the step (S3) is dried at 110° C. for 12 hours, and then calcined at 550° C. for 6 hours to obtain a product, which is recorded as B5.

[0126] Comparative Example 6

[0127] (S1) 1940 g of nano ZnO (particle size 30 nm), 60 g of sodium methyl cellulose, 20 g of tianqing powder, and 200 g of nickel acetate tetrahydrate were mixed to obtain a solid mixture;

[0128] (S2) 490 g of water and the solid mixture obtained in step (S1) were mixed uniformly, and then the material was transferred to a kneader and kneaded twice, and finally placed in an extruder for extrusion molding to obtain a desulfurization catalyst molded body;

[0129] (S3) The desulfurization catalyst molded body obtained in the step (S2) is dried at 110° C. for 12 hours, and then calcined at 550° C. for 6 hours to obtain a product, which is recorded as B6.

[0130] Comparative Example 7

[0131] (S1) 1940 g of nano ZnO (particle size 30 nm), 60 g of sodium methyl cellulose, and 20 g of Tianqing powder were mixed to obtain a solid mixture;

[0132] (S2) dissolving 200 g of nickel acetate tetrahydrate in 490 g of water to obtain a nickel acetate solution;

[0133] (S3) uniformly mixing the nickel acetate solution of Group VIII metal obtained in step (S2) and the solid mixture obtained in step (S1), then transferring the materials to a kneader for kneading twice, and finally placing them in an extruder for extrusion molding to obtain a desulfurization catalyst molded body;

[0134] (S4) The desulfurization catalyst molded body obtained in the step (S3) is dried at 110° C. for 12 hours, and then calcined at 550° C. for 6 hours to obtain a product, which is recorded as B7.

[0135] Comparative Example 8

[0136] (S1) 1940 g of nano ZnO (particle size 30 nm), 60 g of sodium methyl cellulose, and 120 g of nickel acetate tetrahydrate were mixed to obtain a solid mixture;

[0137] (S2) dissolving 80 g of nickel acetate tetrahydrate in 490 g of water to obtain a nickel acetate solution;

[0138] (S3) uniformly mixing the nickel acetate solution of Group VIII metal obtained in step (S2) and the solid mixture obtained in step (S1), then transferring the materials to a kneader for kneading twice, and finally placing them in an extruder for extrusion molding to obtain a desulfurization catalyst molded body;

[0139] (S4) The desulfurization catalyst molded body obtained in the step (S3) is dried at 110° C. for 12 hours, and then calcined at 550° C. for 6 hours to obtain a product, which is recorded as B8.

[0140] Comparative Example 9

[0141] (S1) 1940 g of nano ZnO (particle size 30 nm) and 120 g of nickel acetate tetrahydrate are mixed to obtain a solid mixture;

[0142] (S2) dissolving 80 g of nickel acetate tetrahydrate in 490 g of water to obtain a nickel acetate solution;

[0143] (S3) uniformly mixing the nickel acetate solution of Group VIII metal obtained in step (S2) and the solid mixture obtained in step (S1), then transferring the materials to a kneader for kneading twice, and finally placing them in an extruder for extrusion molding to obtain a desulfurization catalyst molded body;

[0144] (S4) The desulfurization catalyst molded body obtained in the step (S3) is dried at 110° C. for 12 hours, and then calcined at 550° C. for 6 hours to obtain a product, which is recorded as B9.

[0145] Comparative Example 10

[0146] (S1) 1940 g of nano ZnO (particle size of 1 μm), 60 g of sodium methyl cellulose, 20 g of tianqing powder, and 120 g of nickel acetate tetrahydrate were mixed to obtain a solid mixture;

[0147] (S2) dissolving 80 g of nickel acetate tetrahydrate in 490 g of water to obtain a nickel acetate solution;

[0148] (S3) uniformly mixing the nickel acetate solution of Group VIII metal obtained in step (S2) and the solid mixture obtained in step (S1), then transferring the materials to a kneader for kneading twice, and finally placing them in an extruder for extrusion molding to obtain a desulfurization catalyst molded body;

[0149] (S4) The desulfurization catalyst molded body obtained in the step (S3) is dried at 110° C. for 12 hours, and then calcined at 550° C. for 6 hours to obtain a product, which is recorded as B10.

[0150] Comparative Example 11

[0151] (S1) 1940 g of nano ZnO (particle size 30 nm), 60 g of sodium methyl cellulose, 20 g of tianqing powder, and 120 g of cobalt nitrate were mixed to obtain a solid mixture;

[0152] (S2) dissolving 80 g of cobalt nitrate in 490 g of water to obtain a nickel acetate solution;

[0153] (S3) uniformly mixing the nickel acetate solution of Group VIII metal obtained in step (S2) and the solid mixture obtained in step (S1), then transferring the materials to a kneader for kneading twice, and finally placing them in an extruder for extrusion molding to obtain a desulfurization catalyst molded body;

[0154] (S4) The desulfurization catalyst molded body obtained in the step (S3) is dried at 110° C. for 12 hours, and then calcined at 550° C. for 6 hours to obtain a product, which is recorded as B11.

[0155] Comparative Example 12

[0156] (S1) 1940 g of nano-CuO (particle size of 30 nm), 60 g of sodium methylcellulose, 20 g of tianqing powder, and 120 g of nickel acetate tetrahydrate were mixed to obtain a solid mixture;

[0157] (S2) dissolving 80 g of nickel acetate tetrahydrate in 490 g of water to obtain a nickel acetate solution;

[0158] (S3) uniformly mixing the nickel acetate solution of Group VIII metal obtained in step (S2) and the solid mixture obtained in step (S1), then transferring the materials to a kneader for kneading twice, and finally placing them in an extruder for extrusion molding to obtain a desulfurization catalyst molded body;

[0159] (S4) The desulfurization catalyst molded body obtained in the step (S3) is dried at 110° C. for 12 hours, and then calcined at 550° C. for 6 hours to obtain a product, which is recorded as B12.

[0160] Comparative Example 13

[0161] (S1) 1940 g of nano ZnO (particle size 30 nm), 60 g of sodium methyl cellulose, 20 g of tianqing powder, and 120 g of nickel acetate tetrahydrate were mixed to obtain a solid mixture;

[0162] (S2) dissolving 80 g of nickel acetate tetrahydrate in 490 g of water to obtain a nickel acetate solution;

[0163] (S3) uniformly mixing the nickel acetate solution of Group VIII metal obtained in step (S2) and the solid mixture obtained in step (S1), then transferring the materials to a kneader for kneading twice, and finally placing them in an extruder for extrusion molding to obtain a desulfurization catalyst molded body;

[0164] (S4) The desulfurization catalyst molded body obtained in the step (S3) is dried at 110° C. for 12 hours, and then calcined at 300° C. for 6 hours to obtain a product, which is recorded as B13.

[0165] Comparative Example 14

[0166] (S1) 1940 g of nano ZnO (particle size 30 nm), 60 g of sodium methyl cellulose, 20 g of tianqing powder, and 120 g of nickel acetate tetrahydrate were mixed to obtain a solid mixture;

[0167] (S2) dissolving 80 g of nickel acetate tetrahydrate in 490 g of water to obtain a nickel acetate solution;

[0168] (S3) uniformly mixing the nickel acetate solution of Group VIII metal obtained in step (S2) and the solid mixture obtained in step (S1), then transferring the materials to a kneader for kneading twice, and finally placing them in an extruder for extrusion molding to obtain a desulfurization catalyst molded body;

[0169] (S4) The desulfurization catalyst molded body obtained in the step (S3) is dried at 110° C. for 12 hours, and then calcined at 750° C. for 6 hours to obtain a product, which is recorded as B14.

[0170] Test Example

[0171] Test Example 1 Performance Analysis Characterization Test

[0172] The high performance adsorption desulfurization catalyst A1 prepared in Example 1 of the invention and the preparation examples of Comparative Examples 2-4 were subjected to the following performance characterization analysis tests, and the test results are shown in Table 1 and Attached Figure 1-4 middle.

[0173] XRD (X-ray diffraction) structure test: XRD-6000 X-ray diffractometer of Shimadzu Corporation of Japan was used to determine the crystal form and crystallinity of the sample. The test conditions are: (Cu target Ka radiation source, Ni filter), working voltage 40kV, current 30mA, scanning step length 0.02°, wide-angle X-ray diffraction scanning speed 8° / min, scanning range 5~35°; small-angle X-ray diffraction scanning speed 2° / min, scanning range 0.6~5°.

[0174] H2 pulse chemical adsorption test: The sample was subjected to H2 pulse chemical adsorption test using the Autochem∏2920 fully automatic programmed temperature chemical adsorption instrument produced by Micromeritics, USA. During the experiment, the temperature was raised to 200℃ at a rate of 10℃ / min and reduced with H2 for 1h. After the temperature was lowered to 50℃, the excess H2 was purged with a high-purity He gas flow until the baseline was stable, and then the dispersion and particle size of the metal to be tested were measured with an H2-pulse.

[0175] H2-TPR test: The sample was tested by using the Autochem∏2920 fully automatic programmed temperature chemical adsorption instrument produced by Micromeritics, USA. The experimental method of H2-TPR: 0.1g of catalyst was loaded into a U-shaped quartz tube, and the sample was heated to 50°C under 50mL / min argon (pretreatment gas) purge. After stabilization, it was switched to a 10% H2+90% Ar mixed gas. After the baseline was stable, it was heated to 900°C at a rate of 10°C / min, and the change of H2 volume fraction was detected by a thermal conductivity detector (TCD). H2 pulse chemical adsorption method: 0.2g of catalyst was loaded into a U-shaped quartz tube, and the sample was reduced by pure H2 at 400°C for 4h, and then switched to He gas for 1h at this temperature to completely remove H and other adsorbed species on the catalyst surface. When the temperature dropped to 50°C in He gas, H2 pulse adsorption was performed, and the pulse interval time was 3min until the adsorption was saturated. The change of H2 volume fraction was detected by TCD.

[0176] XPS test: The ESCALab 250 instrument (XPS) produced by Thermo Scientific was used to characterize the changes in the electron binding energy and content of W species on the catalyst surface. Experimental method: After taking an appropriate amount of sample and pressing it into a tablet, stick it on the sample plate, put the sample into the sample chamber of the Thermo Scientific K-Alpha XPS instrument, and send the sample into the analysis chamber when the pressure in the sample chamber is less than 2.0×10-7mbar. The spot size is 400μm, the working voltage is 12kV, and the filament current is 6mA; the full spectrum scan energy is 150eV, and the step length is 1eV; the narrow spectrum scan energy is 50eV, and the step length is 0.1eV.

[0177] Figure 1 It is the XRD diagram of the adsorption desulfurization catalyst prepared in Inventive Examples 1-8 and the product prepared in Comparative Example 1. This characterization result reflects the phases and their crystallinity contained in the corresponding test products. Figure 1 The diffraction peaks at 2θ=31.8°, 34.4°, 36.3°, 47.5° and 56.6° (marked with * in the figure) belong to the ZnO phase, and the diffraction peak at 2θ=43.1° (marked with # in the figure) belongs to the NiO phase. There is no obvious difference in the diffraction peaks belonging to ZnO in all the test products, indicating that the different preparation processes and the addition of Group VIII metals in the above embodiments have basically no effect on the structure of the ZnO crystal particles.

[0178] Table 1 NiO dispersion data obtained from H2 pulse chemical adsorption data

[0179] A1 B2 B3 B4 Dispersion of NiO (%) 90.2 73.1 78.9 85.7

[0180] Figure 2 The H2 pulse chemical adsorption diagram of the adsorption desulfurization catalyst prepared in Example 1 of the present invention and the product prepared in Comparative Examples 2-4 is the direct data obtained by H2 pulse chemical adsorption. The dispersion data of NiO is obtained by applying the numerical model based on the data of H2 pulse chemical adsorption, that is, Table 1, that is, Table 1 is the dispersion data of NiO of the samples of Example 1 of the present invention and Comparative Examples 2-4. It can be seen from the analysis that:

[0181] 1) When no multifunctional additive is added during the preparation of the high-performance adsorption desulfurization catalyst (i.e., Comparative Example 2), the dispersion of the NiO active component is the worst;

[0182] 2) When the amount of addition introduced during the preparation of the high-performance adsorption desulfurization catalyst is too low (i.e., Comparative Example 3), the dispersion of the NiO active component is improved, but the effect is limited;

[0183] 3) When the addition amount introduced during the preparation of the high-performance adsorption desulfurization catalyst is too high (ie, Comparative Example 4), the dispersion of the NiO active component is not significantly improved, but is lower than the dispersion of the catalyst prepared using Example 1 of the present invention.

[0184] Figure 3 It is the H2-TPR diagram of the adsorption desulfurization catalyst prepared in Example 1 of the present invention and the products prepared in Comparative Examples 2-4. This characterization result reflects the change in reduction temperature caused by the interaction between the active component NiO and other components in the corresponding test sample. By comparing the change in the reduction peak position, the interaction between NiO and other components in the untested sample can be compared. From the result, it can be seen that the reduction process of NiO mainly occurs in two temperature regions, namely the low temperature region of 350℃-500℃ and the high temperature region above 550℃. However, since the contact between NiO and the ZnO carrier will produce a strong interaction, which makes NiO difficult to be reduced, it can be considered that the reduction peak in the low temperature zone corresponds to the reduction process of NiO that has not contacted the ZnO carrier, and the reduction peak in the high temperature zone corresponds to the reduction process of NiO that has contacted the ZnO carrier, representing the interaction between NiO and the ZnO carrier, that is, by comparing the positions of the reduction peaks in the high temperature zone, the strength of the interaction between NiO and the ZnO carrier in different samples can be compared; and the areas of the two reduction peaks represent the corresponding NiO content, that is, by comparing the reduction peak areas, the content of NiO distributed on the ZnO carrier in different samples can be compared.

[0185] By comparing the results of different samples, we can find that:

[0186] 1) When no multifunctional additive is added during the preparation of the high-performance adsorption desulfurization catalyst (i.e., Comparative Example 2), the interaction between NiO and the ZnO carrier is minimal, and the content of the NiO active component on the ZnO carrier is the lowest;

[0187] 2) When the amount of addition introduced during the preparation of the high-performance adsorption desulfurization catalyst is too low (i.e., Comparative Example 3), the interaction between NiO and the ZnO carrier and the content of the NiO active component on the ZnO carrier are improved, but the effect is limited;

[0188] 3) When the addition amount introduced during the preparation of the high-performance adsorption desulfurization catalyst is too high (i.e., Comparative Example 4), the interaction between NiO and the ZnO carrier and the content of the NiO active component on the ZnO carrier are not improved, but are lower than that of Catalyst A1 prepared using Example 1 of the present invention.

[0189] Figure 4The XPS graphs of the adsorption desulfurization catalyst prepared in Example 1 of the present invention and the products prepared in Comparative Examples 2-4 reflect the change in binding energy caused by the interaction between the active component NiO and other components in the test sample. From the results, it can be seen that the characteristic peak of Ni in NiO is the Ni2p3 / 2 peak with a binding energy of about 857eV. However, since NiO and the ZnO carrier will have a strong interaction when in contact, the Ni 2p3 / 2 peak moves toward the low binding energy direction, so the more the peak moves toward the low binding energy direction, the stronger the interaction between NiO and the ZnO carrier.

[0190] By comparing the results of different samples, we can find that:

[0191] 1) When no multifunctional additive is added during the preparation of the high-performance adsorption desulfurization catalyst (i.e., Comparative Example 2), the interaction between NiO and the carrier ZnO is minimal;

[0192] 2) When the amount of addition introduced during the preparation of the high-performance adsorption desulfurization catalyst is too low (i.e., Comparative Example 3), the interaction between NiO and the carrier ZnO is improved, but the effect is limited;

[0193] 3) When the amount of addition introduced during the preparation of the high-performance adsorption desulfurization catalyst is too high (i.e., Comparative Example 4), the interaction between NiO and the carrier ZnO is lower than the interaction in the catalyst prepared using Example 1 of the present invention;

[0194] It can be seen from the above results that the amount of each component used in the preparation process of the present invention cannot be obtained by reasonable inference, and the results are not obtainable by reasonable inference. They are all specific settings of the present invention. Therefore, in order to obtain a high-performance adsorption desulfurization catalyst, it is necessary to strictly control the parameters involved in the preparation process.

[0195] Test Example 2 Desulfurization Performance Test

[0196] The high-performance adsorption desulfurization catalysts A1-A8 prepared in Examples 1-8 of the invention and the products B1-B14 prepared in Comparative Examples 1-14 were subjected to gasoline adsorption desulfurization performance evaluation experiments, and the test results are shown in Table 2 below. Before conducting the gasoline adsorption desulfurization activity and sulfur capacity evaluation experiment, the test samples need to be pretreated, and the specific steps of the pretreatment are: 2.0 g of the high-performance adsorption desulfurization catalysts A1-A8 prepared in Examples 1-8 of the invention and the products B1-B14 prepared in Comparative Examples 1-14 were respectively weighed and loaded into a fixed bed reactor, and H2 atmosphere was used at a temperature of 400°C, a H2 partial pressure of 0.1 MPa, and a H2 volume space velocity of 360 h -1 It was pretreated under the conditions of , and the treatment time was 24h.

[0197] The specific steps of the gasoline adsorption desulfurization activity and sulfur capacity evaluation experiment are as follows: using H2 atmosphere at a temperature of 350℃, a H2 partial pressure of 1.0MPa, and a raw material volume space velocity of 2.0h -1 Under the conditions of H2 and raw material volume ratio of 25:1, a gasoline raw material with a sulfur content of 200 mg / L was introduced for adsorption desulfurization. The sulfur content of the gasoline product was measured after the reaction for 24 hours, which was used as an indicator for evaluating its desulfurization activity. When the sulfur content of the gasoline product was higher than 100 ng / Kg, the adsorption desulfurization reaction was stopped, and the reaction time was recorded. This was used as an indicator for evaluating its sulfur capacity. The results are shown in Table 2.

[0198] Table 2 Desulfurization performance test

[0199]

[0200]

[0201] It can be seen from Table 2 that the adsorption desulfurization catalysts of Examples 1-8 of the present invention can reduce the sulfur content in the raw gasoline to below 100 ng / Kg, and keep the sulfur content reduced to 100 ng / Kg for more than 300 days. Compared with the comparative example, the adsorption desulfurization catalysts obtained in the examples of the present invention have significant improvements in both desulfurization activity and sulfur capacity, especially in terms of desulfurization activity, which can reduce the sulfur content of the raw gasoline to below 100 ng / Kg, indicating that the prepared adsorption desulfurization catalyst has a particularly excellent effect in terms of desulfurization activity. Combined with the simplicity of the preparation method of the present invention, it is not necessary to have too much process control, so it can be considered that the high-performance adsorption desulfurization catalyst of the present invention will have extremely excellent application prospects.

[0202] In addition, in the preparation method of the present invention, whether it is the amount and type of each raw material such as multifunctional additives, lubricants, etc. added or the setting of each parameter in the preparation process, it affects the performance of the adsorption desulfurization catalyst, specifically as follows.

[0203] Comparative Examples 1-12 adopt a series of parameter settings different from those of the present invention: replacing the Group VIII metal from Ni with Co, replacing the Group IIB metal from Zn with Cu, not adding Group VIII metal oxides, introducing all Group VIII metal oxides only in the form of solid or liquid, too much or too little multifunctional additives, too little lubricant, replacing the multifunctional additives with starch, and replacing the Group VIII metal oxides with nano-scale particles with non-nano-scale particles, all of which significantly reduce the desulfurization performance of the obtained adsorption desulfurization catalyst, and the performance reduction is not only reflected in the desulfurization activity but also in the sulfur capacity, that is, the products obtained in Comparative Examples 1-12 do not meet the standard in the desulfurization activity of the raw gasoline desulfurization process, and the sulfur capacity is also significantly reduced.

[0204] It should also be noted that when calcining at the end, if the calcination temperature is too high or too low, the performance of the product will be affected. The reason may be that if the calcination temperature is too low, the lubricant and multifunctional additive cannot be removed, which will easily lead to blockage of the pores of the formed adsorption desulfurization catalyst, affecting its diffusion performance, and will make the combination of NiO and ZnO insufficient, resulting in less interaction between the two types of metal oxides, thus affecting its desulfurization performance. If the calcination temperature is too high, NiO may agglomerate on the carrier ZnO, resulting in a decrease in the adsorption desulfurization performance of the catalyst.

[0205] According to the disclosure and teaching of the above description, those skilled in the art to which the present invention belongs may also make changes and modifications to the above embodiments. Therefore, the present invention is not limited to the specific embodiments disclosed and described above, and some modifications and changes to the invention should also fall within the scope of protection of the claims of the present invention. In addition, although some specific terms are used in this specification, these terms are only for the convenience of description and do not constitute any limitation to the present invention.

Claims

1. A method for preparing an adsorptive desulfurization catalyst, characterized in that: The following steps are involved: (S1) uniformly mixing a Group IIB metal oxide, a multifunctional additive, a lubricant and a soluble salt of a Group VIII metal to obtain a solid mixture; The Group IIB metal oxide is zinc oxide, and the particle size of the Group IIB metal oxide is 20-50 nm; The multifunctional auxiliary agent is one or more of sodium carboxymethyl cellulose, potassium carboxymethyl cellulose, sodium alginate, sodium polyacrylate, and sodium carboxyethyl cellulose; The mass ratio of the IIB group metal oxide to the multifunctional additive is (30-40):1; The lubricant is graphite powder or sesbania powder; The Group VIII metal is nickel; (S2) dissolving a soluble salt of a Group VIII metal in water to obtain a soluble salt solution of a Group VIII metal; (S3) the solid mixture obtained in step (S1) and the soluble salt solution of the Group VIII metal obtained in step (S2) are mixed uniformly and molded to obtain a desulfurization catalyst molded body; (S4) Drying and calcining the desulfurization catalyst molded body obtained in the step (S3) at a calcination temperature of 550-600° C. to obtain the adsorption desulfurization catalyst.

2. The method according to claim 1, characterized in that The amounts of the Group IIB metal oxide, the multifunctional additive, the lubricant and the soluble salt of the Group VIII metal in the step (S1) are, in parts by weight, respectively: 100-200 parts of Group IIB metal oxide; 5-10 parts of multifunctional additives; 1-4 parts of lubricant; 5-30 parts of soluble salt of Group VIII metal.

3. The method according to claim 1, characterized in that The amounts of the Group IIB metal oxide, the multifunctional additive, the lubricant and the soluble salt of the Group VIII metal in the step (S1) are, in parts by weight, respectively: 190-200 parts of Group IIB metal oxide; 5-10 parts of multifunctional additives; 1-4 parts of lubricant; 5-30 parts of soluble salt of Group VIII metal.

4. The method according to claim 1, characterized in that The multifunctional auxiliary agent in the step (S1) is sodium carboxymethyl cellulose.

5. An adsorption desulfurization catalyst, characterized in that: The adsorption desulfurization catalyst is prepared by the method according to any one of claims 1 to 4, and is composed of zinc oxide and nickel oxide.

6. The use of the adsorptive desulfurization catalyst according to claim 5, characterized in that: The application is for desulfurization of sulfur-containing liquids.

Citation Information

Patent Citations

  • C 4 olefin desulfurization absorbent and production method and use thereof

    CN101450302B

  • Ultra-deep desulfurization absorbent containing C 4 conjugated dienes raw material and production method and use thereof

    CN101450303A

  • Gasoline desulfurization adsorbent and preparation and application thereof

    CN102407094B

  • Gasoline ultra-deep desulfurization adsorbent and application thereof

    CN103721668A

  • Fractional oil desulfurizing and adsorption agent and its preparation method

    CN1461796A